Vitality and Interest-Enjoyment as a Function of Class-to-Class Variation in Need-Supportive Teaching and Pupils' Autonomous Motivation - Mouratidis, A. A.; Vansteenkiste, M.; Sideridis, G.; Lens, W. (Journal of Educational PsychologyJournal of Educational Psychology, 2011)
In 2 quasi-experimental field studies in a real-life physical education (PE) setting, the authors investigated whether the interest-enjoyment and vitality of Greek pupils (age range, 10-12 years) varied from class-to-class as a function of the class-to-class variation in the manipulated motivational environment (Studies 1 and 2) and pupils' relative autonomous motivation (Study 2). In Study 1, multilevel analyses showed at the within-student level that students (N = 138, 48.6% boys and 51.4% girls) reported, on average, more interest-enjoyment and vitality after a need-supportive, relative to a typical (i.e., control group), PE class. This main effect was replicated in Study 2 (N = 155, 53.6% boys and 46.4% girls), and Study 2 findings further showed at the between-student level that interest-enjoyment was somewhat higher among pupils scoring higher in relative autonomous motivation. Moreover, Study 2 provided evidence for an interaction effect such that pupils with high, as compared with those with low, relative autonomous motivation benefited significantly more from a need-supportive class. Perceived need support was found to fully explain the effects of manipulated need support on interest-enjoyment and vitality. Results are discussed within the self-determination theory (Deci & Ryan, 2000).